Evolution of skyrmion crystals in Fe0.5Co0.5Si-like quasi-two-dimensional ferromagnets driven by external magnetic field and temperature. (February 2020) - Liu, Zhaosen; Huan, Tiantian; Ian, Hou
Abstract: Magnetic skyrmions have attracted great research interest in recent years due to their exotic physical properties, scientific merit and potential applications in modern technology. Here, we apply a quantum computational method to investigate the spin configurations of Fe0.5 Co0.5 Si-like quasi-two-dimensional ferromagnetic system with co-existence of Dzyaloshinskii–Moriya and Heisenberg exchange interactions. We find that within a weak magnetic field perpendicular to the film plane, skyrmion crystal (SkX) of hexagonal-close-packed pattern can be induced, the spin configurations evolve with applied magnetic field and temperature. This quantum model, if scaled, is able to qualitatively reproduce the experimental results of SkX with long periodicity. Especially, when the skyrmion size is around a few nano-meters in diameter, or more general, when the characteristic length of the material approaches the lattice scale, the quantum model is expected to be more accurate than the classical ones. Highlights: A quantum model is scaled to simulate the chiral spin textures in 2D systems. SkX can be induced by an applied magnetic field when it is sufficiently strong. To stabilize the SkX texture, a skyrmion is usually surrounded by four vortices. The winding number density of a SkX also forms almost identical lattice. The simulated spin textures evolves with applied magnetic field and temperature.